An investigation of influence of solvent on the degradation kinetics of carotenoids in oil extracts of Calendula officinalis - Bezbradica Dejan I.; Milić-Aškrabić Jela; Petrović Slobodan D.; Šiler-Marinković Slavica (Journal of the Serbian Chemical Society, 2005)
The stability of carotenoids was studied in marigold oil extracts prepared with following solvents: Myritol 312®, paraffin oil, almond oil, olive oil, sunflower oil, grape seed oil, and soybean oil. The concentration of the carotenoids was determined by spectroscopic measurement at 450 nm. Degradation rate showed a first order dependence on the concentration of carotenoids with a faster first stage (which lasted 35-50 days, depending on the solvent) and a slower second stage. The highest degradation rates were observed in extracts prepared with linoleic acid rich solvents (sunflower oil, soybean oil and grape seed oil), while the lowest were found in oil with saturated fatty acids (Myritol 312®) and paraffin oil. These results confirm the connection between the degradation of carotenoids and lipid autoxidation, and suggest that the influence of the oil solvents on the stability of oil extracts of Calendula officinalis is a factor that must be considered when selecting a solvent for the production of marigold oil extracts.